Analysis on Mixed Lubrication Performance of Pin-bush Pairs in Large-sized Marine Chain - Liu Yi; Liu Xiaoling; Liu Guoliang; Li Qun (Jixie chuandong)
To investigate the issue of wear in the roller chain of high-power marine equipment engines, an analysis of the motion characteristics of the pin-bush pair was conducted. A model of thermal mixed lubrication of the pin-bush pair was established to study the effects of the equivalent curvature radius, the entrainment velocity, the surface roughness, etc. on the mixed lubrication performance of the roller-chain. The results show that when the large-sized roller-chain assembly operates under low-speed and light-load conditions, the pin-bush pair is essentially in a hydrodynamic lubrication state, and thermal effects can be neglected. No significant scale effect is induced by the equivalent curvature radii. In the startup and shutdown phases, the high friction coefficient between the pin and the bushings, along with the higher contact load, places the contact pair in a mixed lubrication regime, making it susceptible to wear. Higher surface roughness requires a higher entrainment velocity to maintain the contact pair in a hydrodynamic lubrication. As the roughness increases, the friction coefficient also increases, and the film thickness ratio decreases, leading to a worse lubrication state. Due to the low speed, the pin and bush are in a mixed or even boundary lubrication state. Surface hardness has a certain impact on the friction coefficient and maximum oil film temperature rise. In addition, the lubricating status is influenced by the environment viscosity.